PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH (STUDI PADA BANK RIAU KEPRI CABANG PASIR PENGARAIAN) - Puspitasari, Dian; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research was conductedin Riau Kepri Bank, Pasir Pengaraian branch. this research aimsto determine the effect of service quality loward customer satisfaction. Service quality as independent variable(x) and customer satisfaction as independent variable (y). The research sample are 99 respondents of the population by using the slovin formula. Data was obtained from the questionnaire and subsequently processed to then be tested with the help of statistics through SPSS. The result of. calculation of the determination coefficientis 0.670. it means, service quality affects customer satisfaction is 67%. Keywords: Service quality, customer satisfaction, Riau Kepri Bank